Mechanism of Sishen Pills-Tongxie Yaofang in the treatment of ulcerative colitis based on network pharmacology and experimental verification - Haifan Liu; Xue Feng; Dunfang Wang; Li Liu; Yaqing Liu; Bin Liu; Lin Zhu; Caijuan Zhang; Weipeng Yang (Science of Traditional Chinese Medicine)
Abstract. Background. Ulcerative colitis (UC) is a diffuse nonspecific intestinal inflammation. Spleen-kidney Yang deficiency combined with liver stagnation is the most common symptom. Sishen Pills-Tongxie Yaofang (SSP-TXYF) is a traditional Chinese medicine (TCM) that is widely used in the treatment of this symptom. However, its pharmacological mechanism and active components remain unclear. Objective. This study elucidated the potential mechanism and active components of SSP-TXYF in the treatment of UC from the perspective of TCM syndrome. Methods. Metascape, STRING, and Cytoscape were used to explore the SSP-TXYF-compound-target-UC network and biological enrichment pathways, so as to screen the active compounds, key targets, and pathways of SSP-TXYF. Through the construction of a rat model with UC, the key targets and active components were verified after SSP-TXYF administration. Results. A total of 77 effective active chemical components, 208 potential targets, and 5 core target genes were screened out. Gene Ontology biological process items and Kyoto Encyclopedia of Genes and Genomes signaling pathways showed that SSP-TXYF played a role in regulating nerve-endocrine, cell proliferation and apoptosis, and immune-related pathways. The main compounds and the target protein exhibited a good binding ability in molecular docking. The results of animal experiments showed that SSP-TXYF could improve UC through IL-6, AKT1, PTGS2, CASP3, and JUN, and nobiletin and wogonin were identified as the main active components. Conclusions. This study suggests that nobiletin and wogonin are the main components of SSP -TXYF in the treatment of UC, which provides effective therapeutic targets and drugs for future clinical treatment of UC.